EVALUASI KUALITAS PEMBELAJARAN DARING MELALUI SISTEM MANAJEMEN PENDIDIKAN DI SEKOLAH DASAR - Erina Fatihah; Marsha Dilla; Salsabilla Azzahra; Arita Marini (Bajang Institute, 2024)
Online learning has become an important part of the education system today, especially in facing the challenges faced by the COVID-19 pandemic. However, to ensure the effectiveness and quality of online learning, ongoing evaluation needs to be carried out. This research aims to evaluate the quality of online learning through the education management system in elementary schools. The research method used is an evaluation study with a qualitative approach. Data was collected through direct observation of the implementation of online learning, interviews with teachers and students, as well as analysis of documents related to the education management system. The participants in this research were teachers and students from several elementary schools that implemented online learning. The research results show that there are various factors that influence the quality of online learning, including the availability of technological infrastructure, teacher competence in managing online learning, parental involvement, and support from the school. An effective education management system also plays an important role in facilitating the implementation of quality online learning. Based on these findings, it is recommended that schools continue to evaluate and update the education management system, increase training and support for teachers in managing online learning, and actively involve parents in supporting online learning. In addition, the government and related institutions need to provide greater support in providing adequate technological infrastructure and affordable internet access for all students